The Relationship Between Chronic Kidney Disease and Sarcopenia: A Systematic Review - Eppy Setyowati; Ragil Putri Fitriyanti; Aldila Ayu Widya; Justinho Soares (Indonesian Journal of Global Health Research, 2026)
Chronic kidney disease (CKD) is a growing global health problem and is associated with multiple systemic complications. One important but often underrecognized complication is sarcopenia, characterized by progressive loss of muscle mass, strength, and physical performance. Sarcopenia is highly prevalent in patients with advanced CKD and those undergoing hemodialysis and is associated with poor clinical outcomes, including increased hospitalization, functional decline, and mortality. This literature review aimed to synthesize recent evidence on the relationship between CKD and sarcopenia, including prevalence, contributing factors, pathophysiological mechanisms, and clinical implications. This review followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Literature searches were conducted in PubMed, ScienceDirect, Google Scholar, and Semantic Scholar for English-language articles published between 2020 and 2025. Study selection was guided by the PICOS framework. Methodological quality was assessed using the Joanna Briggs Institute (JBI) Critical Appraisal Checklist. A total of 15 studies meeting the inclusion criteria were included in the final synthesis. The included studies reported a high prevalence of sarcopenia among CKD patients, ranging from 15.9% to 64.1%, with higher rates observed in advanced CKD stages and hemodialysis populations. Sarcopenia was consistently associated with older age, malnutrition, protein–energy wasting, chronic inflammation, reduced physical activity, and metabolic disturbances. Clinically, sarcopenia was linked to increased mortality, hospitalization, reduced physical function, and poorer quality of life. Sarcopenia is a prevalent and clinically significant complication of CKD. Early detection and integrated interventions combining nutritional optimization, resistance exercise, and metabolic management are essential to improve patient outcomes. Further longitudinal studies are needed to strengthen preventive and therapeutic strategies.